Genetic tracking of Crimean-Congo haemorrhagic orthonairovirus in Hyalomma population infesting cattle in Nigeria - Oluwafemi Babatunde Daodu; Joseph Ojonugwa Shaibu; Rosemary Ajuma Audu; Daniel Oladimeji Oluwayelu (PLoS ONE, 2025)
Crimean-Congo haemorrhagic fever virus (CCHFV), a Biosafety level 4 pathogen transmitted by ticks, causes severe haemorrhagic diseases in humans but remains clinically silent in animals. Over the past forty years, Nigeria lacks comprehensive genetic data on CCHFV in livestock and ticks. This study aimed to identify and characterize CCHFV strains in cattle and their Hyalomma ticks, the primary vector, in Kwara State, Nigeria. Blood samples and Hyalomma ticks were collected from cattle, with ticks identified to species, pooled, and homogenized for RNA extraction. The CCHFV S-segment was detected using specific primers via reverse transcriptase polymerase chain reaction, followed by sequencing of amplicons. Among 318 cattle, 318 sera samples and 2855 Hyalomma ticks (H. dromedarii (49.0%), H. truncatum (44.5%), and H. rufipes (6.5%)) were obtained. Only two tick pools of H. truncatum tested (2/319 pools) were positive for CCHFV, with no positive cattle sera detected. The sequenced positive pools, denoted as CCHFV/NGR/ILN/2021/F22_S-segment (1228 bp) and CCHFV/NGR/ILN/2021/F101_S-segment (863 bp), showed 98.21% nucleotide identity with 15 variations. These strains shared 98.13% and 98.93% nucleotide identity with CCHFV IbAr10200/UCCR4401 isolated from Nigerian ticks, but only 93.88% and 93.63% similarity with CCHFV isolated in 2016 from humans in Nigeria. Additionally, compared to CCHFV isolate IbAr10200 (KY484036), sequences from this study exhibited 9–23 nucleotide variable positions with 3–4 non-synonymous amino acid replacements. Phylogenetic analysis revealed clustering of these strains around IbAr10200, suggesting ongoing circulation. This study underscores the need for broader surveillance to understand the full spectrum of CCHFV strains and clades circulating in Nigeria.